ANALISIS PENGARUH PEMBERIAN INSENTIF DAN LINGKUNGAN KERJA NON FISIK TERHADAP MOTIVASI KERJA DAN DAMPAKNYA PADA KINERJA KARYAWAN (Studi Pada BRI Kantor Cabang Pattimura) - Ardiani, Astrid; Nugraheni, Rini (Diponegoro Journal of Management, 2015)
This study aims to determine whether the incentives and non-physical work environment affected the motivation of employees and analyze its impact on the performance of employees in BRI Branch Office Pattimura. This research population refers to the employees of BRI Branch Office Pattimura. Samples taken by are 110 respondents using Non-Probability Sampling technique where not all members of the population in the same position have the opportunity to be selected into the sample.The results of this study indicate that non-physical work environment has a significant possitive influence on the motivation, incentives has a negative influence on the motivation and performance of employees, non-physical work environment and motivation have no significant positive effect on employee performance. The highest influential variable on work motivation and employee performance was non-physical work environment. This equation model has Chi-square value of 39.855 with the probability value above than the recommendation 0.05, and the value was 0,068.